Knowledge management for innovation and rural development: : experiences from Costa Rica - Barboza Arias, Luis Miguel (2020)
The objective of the article is to review the conceptual evolution of knowledge management and then analyze itsoperationalization in two extension experiences in Costa Rica. Case studies are used as a methodological tool and the approach to agricultural innovation systems is used as an analytical lens. It is proposed that rural knowledge management is a relatively new phenomenon in Costa Rica. Nevertheless, the initiatives presented seek a paradigm shift that improves the approach to the most complex rural problems. It concludes with some limitations of the study and elements to advance in the construction of a research agenda on the subject.